RĂSPUNDEREA PENALĂ PENTRU INFRACŢIUNILE LEGATE DE PRELEVAREA ORGANELOR SAU ŢESUTURILOR UMANE ÎN STATELE DIN SISTEMUL ANGLO-SAXON - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2007)
The necessity of the investigation of the crimes concerning drawing of the human organs and textures, in the states from the common-law system, is based on surprising of the correlation between national criminal law with foreign models of the specific incrimination, not only through different legal-criminal settlements of these types of crimes, but especially through conferring of the priority to the judicial precedent. Nevertheless in these systems the law did not have so important a character in relation with judicial precedent, but the paradox consists in the fact, that in these states for the first time appear the legal settlements regarding action of drawing of the human organs and textures. In general these regulations did not introduce proper settlements in this domain, but however these establish a constant and real jurisprudence in this frame.